The Effectiveness of the Kaiza Method in Facilitating Children to Memorize and Understand the Quran through Kinesthetic Movement at SDIT al-Fatih in Makassar City - Mardyawati Y (Lembaga Sembilan Tiga Community, 2021)
This study discusses the importance of teaching the Quran at an early age and the appropriate method to facilitate children in memorizing and understanding the meanings of Quranic verses. The method used in this study is the Kaisa method, which emphasizes memorization and understanding of Quranic verses and their translations through kinesthetic movements that are tailored to the meaning of each verse. The purpose of this research is to examine the effectiveness of the Kaisa method in facilitating children to memorize and understand Quranic verses. The results of the study show that the Kaisa method can help children in memorizing and understand the meanings of Quranic verses. This method enables children to easily memorize Quranic verses and understand them through kinesthetic movements that are tailored to the meaning of each verse. Moreover, this research shows that selecting the appropriate teaching method is crucial in achieving learning objectives and should be tailored to the characteristics of students, the number of students, and the learning objectives set by the teacher. The Kaisa method is one effective teaching method to facilitate children in memorizing and understanding the meanings of Quranic verses through kinesthetic movements that are tailored to the meaning of each verse.